Essential trace elements selenium, zinc, copper, and iron concentrations and their related acute-phase proteins in patients with vivax malaria - Seyrek, A; Kocyigit, A; Erel, O (Springernature, 2005)
The aim of the present study is to evaluate the status of plasma essential trace elements selenium (Se), zinc (Zn), copper (Cu), and iron (Fe) concentrations and their related acute-phase proteins, ceruloplasmin (Cp), ferritin, transferrin (Tf), and albumin levels in patients with vivax malaria. Plasma Cu and Zn concentrations were determined by atomic absorption spectrometry (AAS). Se concentrations were determined by graphite furnace AAS. Fe, Cp, Tf, and albumin levels were determined by colorimetric methods. Plasma Se, Fe, and albumin levels were found to be significantly lower (p < 0.01, p < 0.001, and p < 0.05, respectively) and Cu, Cp, and ferritin levels and Cu/Zn ratios were significantly higher (p < 0.001, p < 0.001, p < 0.001, and p < 0.05, respectively) in patients when compared with those of healthy subjects. Plasma, Tf, and Zn levels were not found to be significantly different (p > 0.05) in patients and controls. There were positive important correlations between Cu and Cp (r = 0.908, p < 0.001), Zn and albumin (r = 0.633, p < 0.001), and negative correlations between Fe and ferritin content (r = -0.521, p < 0.05) and Fe and Tf (r = -0.616, p < 0.01) in the patients group. Our findings demonstrated that plasma essential trace elements Se, Cu, and Fe change, but these changes might be dependent on acute-phase proteins, which were regulated as a part of defense strategies of the organism, induced by hormonelike substances.
Keywords: selenium; copper; iron; zinc; ferritin; ceruloplasmin; malaria